1991
DOI: 10.3109/00365519109091633
|View full text |Cite
|
Sign up to set email alerts
|

Modifications induced by gestational diabetes mellitus on cellular membrane properties

Abstract: Alterations in erythrocyte plasma membrane properties (enzymatic activities and membrane fluidity) have been observed in patients affected by insulin-dependent diabetes mellitus (IDDM) and non-insulin-dependent diabetes mellitus (NIDDM). In order to verify whether these alterations are present also in gestational diabetes mellitus (GDM) we studied the plasma membranes obtained from two different cellular types (erythrocyte from both mother and cord blood and placenta syncytiothrophoblast cell) of 16 healthy pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Our data show that GDM placentas have higher AMPK levels compared with the control placentas, whereas the COX4 levels and ATPase activity are similar between both groups. It is important to take into account that the activity that we determined represents the activity of all the ATPase in the placenta, and specifically the Na+/K(+)-ATPase activity was reduced in placental syncytiotrophoblast cells of GDM patients [27]. Is has been described that AMPK is a key for signaling kinases to induce GLUT4 expression and to increase glucose uptake in muscles [28], whereas the complex IV activity has been closely associated with mitochondrial oxidative phosphorylation capacity [29].…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that GDM placentas have higher AMPK levels compared with the control placentas, whereas the COX4 levels and ATPase activity are similar between both groups. It is important to take into account that the activity that we determined represents the activity of all the ATPase in the placenta, and specifically the Na+/K(+)-ATPase activity was reduced in placental syncytiotrophoblast cells of GDM patients [27]. Is has been described that AMPK is a key for signaling kinases to induce GLUT4 expression and to increase glucose uptake in muscles [28], whereas the complex IV activity has been closely associated with mitochondrial oxidative phosphorylation capacity [29].…”
Section: Discussionmentioning
confidence: 99%
“…Whether the ratio of insulin to plasma glucose manipulates the fatty acid transport process in gestational diabetes is unknown. However, modification of membrane properties such as Na+/K+ ATPase activities and reorganization of membrane cholesterol and phospholipids has been reported in erythrocytes and placenta from gestational diabetes [30]. More recently, it has been reported that expression of the genes for fatty acid transport was up‐regulated, whilst genes for lipoprotein lipase were down‐regulated in the placenta of women with gestational diabetes [31].…”
Section: Discussionmentioning
confidence: 99%
“…Other characteristics of GDM placentae possibly cause reduced nonfacilitated diffusion. For example, placentae from GDM pregnancies have been shown to have increased cytotrophoblastic cell numbers, thickening of the basement membrane and reduced vascularisation of the villi [20,21], as well as reduced syncytiotrophoblast membrane fluidity and increased cholesterol content [37]. One study found a 35 to 45 % reduction in uteroplacental blood flow in diabetic pregnancies and the authors suggested this was due to a reduced intravillous space [38].…”
Section: Discussionmentioning
confidence: 99%